Everything Sharks - Musgrave, Ruth 1960- (Washington, D.C. : National Geographic, 2011)
"In Everything Sharks, exciting photos depict great whites, hammerheads, and more. Scientists tell hair-raising tales about encounters. With its awesome facts and action-packed images, this book brings kids close to the mysterious lives of sharks."--Amazon.com.
At head of title: National Geographic kids
Includes bibliographical references (p. 62) and index.
008-012.
Keywords: Sharks -- Juvenile literature; Sharks